Atmosphere Comfort Level Detector Using Humidex: https://doi.org/10.46610/JOEDE.2023.v09i01.001 - Aiswariya P; Anishma Krishnadas; Anupama J; Aysha Ashraf; Remya V (Journal of Electronic Design Engineering, 2023)
Human comfort level detection is always strenuous to assess every day and objectively. Atmospheric comfort level plays an indispensable role in reinforcing productivity in conjunction with convalescent health and safety. The human comfort zone points out a condition of mind that expresses satisfaction with its surrounding. An individual’s comfort level depends on both temperature and humidity, at increased humidity the body’s cooling system on the skin is considerably reduced. To determine temperature and humidity, we employ the DHT11 sensor, then the findings are handed out to Arduino thereafter both temperature and humidity is computed. Calculating humidex values from temperature and dew point data by combining the effects of heat and humidity, the humidex (short for humidity index) is a numerical indicator that indicates how hot it is on average for a certain person. According to the output received from Arduino (humidex), LED is made to blink (LEDs are preassigned according to humidex ranges). The trump card of the detector is that it is economical, and helps to get a better understanding of the degree of excessive heat on the human body and how uncomfortable the current condition is to an average person. This method makes it possible to more effectively communicate the dangers of excessive heat to the human body, transmit how warm it feels to the average person today, and maintain healthy living circumstances. However, this system is unable to show temperature and humidity readings.